2017
DOI: 10.1016/j.vaccine.2016.09.073
|View full text |Cite
|
Sign up to set email alerts
|

System redesign of the immunization supply chain: Experiences from Benin and Mozambique

Abstract: Benin and Mozambique are undertaking system redesign in order to respond to constraints identified in the vaccine supply chain. Results and learnings show improvements in supply chain performance and make a strong case for system redesign. These countries demonstrate the feasibility of system redesign for other countries considering how to address outdated supply chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…Four studies met our inclusion criteria-three before-after studies and one randomized trial. 4,[22][23][24] The reasons for excluding the three remaining studies 21,25,26 are provided in Table 1. Figure 1 is a flow diagram showing the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies met our inclusion criteria-three before-after studies and one randomized trial. 4,[22][23][24] The reasons for excluding the three remaining studies 21,25,26 are provided in Table 1. Figure 1 is a flow diagram showing the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…The second study showed that redesigning a supply chain from a four-level system to a three-level system can improve vaccine availability and reduce stock-outs. 22 The redesigned process reduces the complexity of getting vaccines from the highest level in the supply chain to health facilities. This process resulted in an informed push system, in which vaccines are supplied from the higher levels of the supply chain to the health facilities, which is often informed by the level of consumption in these facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fixing such flaws is not necessarily an overwhelming and cost prohibitive task. For example, published work in Benin9 15 19 has shown that re-designing the immunisation supply chain can actually end up saving money immediately and over time due to gains in efficiency.…”
Section: Discussionmentioning
confidence: 99%